Haemostasis and pregnancy - Franchini, Massimo (Thrombosis and Haemostasis, 2006)
Normal pregnancy is associated with profound alterations in the coagulation and fibrinolytic systems. While these physiological procoagulant changes are aimed to minimise intrapartum blood loss, they do increase the risk of thromboembolism during pregnancy and the post-partum period. In contrast and more rarely, haemorrhage due to an underlying inherited or acquired bleeding disorder may occur and complicatea pregnancy. Based on an analysis of the literature data, this review presents an overview of the main thrombotic and haemorrhagic disorders complicating pregnancy.
Keywords: Haemostasis; thrombophilia; bleeding; pregnancy